2014
DOI: 10.1016/j.bjbas.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chemical composition and antimicrobial activity study of essential oils from two imported lemon fruits samples against pathogenic bacteria

Abstract: a b s t r a c tThe aim of this work to isolate and identify two essential oils by hydro distillation method from two imported lemon fruits samples collected from local supermarket and evaluate their antimicrobial activity against pathogenic bacteria through disc diffusion method. The essential oil was obtained from Turkish and Indian lemon fruits samples by hydro distillation method using Clevenger type apparatus. Both isolated essential oils were identified by GCeMS and determine their in vitro antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…These compounds can be quickly evaporated at room temperature due to their volatility, and they are responsible for the characteristic aroma present in LEO. The results obtained in this work are in agreement with previous chemical compositions identified by other authors [ 7 , 18 ], who reported the presence of alkaloids, mono and sesquiterpenoids, acyclic and cyclic hydrocarbons, phenolic and polyphenolic derivatives and their oxygenated derivatives [ 6 , 34 , 35 , 36 ]. EOs composition and concentration of ingredients depend on different factors, such as geographical distribution; citrus variety and environmental conditions such as temperature, precipitations, hours of sunshine and altitude [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…These compounds can be quickly evaporated at room temperature due to their volatility, and they are responsible for the characteristic aroma present in LEO. The results obtained in this work are in agreement with previous chemical compositions identified by other authors [ 7 , 18 ], who reported the presence of alkaloids, mono and sesquiterpenoids, acyclic and cyclic hydrocarbons, phenolic and polyphenolic derivatives and their oxygenated derivatives [ 6 , 34 , 35 , 36 ]. EOs composition and concentration of ingredients depend on different factors, such as geographical distribution; citrus variety and environmental conditions such as temperature, precipitations, hours of sunshine and altitude [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…Table 2 also shows limonene as a major citrus constituent present in all of the afforded oils at high percentages of the overall composition, ranging from 12.0 to 52.5%. This result agrees with those reported in the literature, where lemon peel cultivated in Brazil contained 70.8% limonene, while Indian and Polish oils showed 53.6% and 48.3%, respectively [10,12,13]. Limonene is well known as an antiviral agent and for its ability to detoxify the liver and prevent tumor development [36].…”
Section: Discussionsupporting
confidence: 91%
“…It is an important medicinal plant cultivated mainly for its juice and spice [2]. Like many citrus fruits, C. limon is known to contain phytochemicals, ranging from fatty acids to phenolics and flavonoids (catechin, rutin, hesperidin, and naringin), pectin, and EO compounds such as limonene, α-terpineol, γ-terpinene, 4-terpineol, α-phellandrene, β-myrcene, α-pinene, β-linalool, and α-selinene [10][11][12][13][14][15].The fruit peel and leaves from Lisbon lemons have been reported for several biological properties, including antioxidant, antibacterial, antifungal, anticancer, and antiviral activities [16]. Lemon peel oil is beneficial to the skin when consumed orally or applied externally for it rejuvenates the skin, keeps it shining, protects it from infections, and reduces body odor [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported LEO antimicrobial properties, acting effectively against a variety of micro-organisms (Moosavy et al, 2017;Al-Jabri and Hossain, 2014). Figure 3 illustrates the variations in lactic acid bacteria during the conservation period at 4°C, in both unflovored and flavored fresh cheese.…”
Section: Evolution Of Microbiological Parameters and Lactic Acid Bact...mentioning
confidence: 99%